PRODUCTION OF AMYLASE ENZYME BY ISOLATED BACTERIAL STRAIN PANTOEA GAVINIAE FROM BOMBYX MORI: Life Sciences-Biotechnology - DINESH.R; HARIPRIYA.R; SELVARAJ.C; DR.P.THIRUMALAIVASAN (International Journal of Life Science and Pharma Research, 2022)
Amylases are classes of enzymes capable of digesting starch and has wide range of industrial applications from food to effluent treatment. The aim of study is to isolate starch degrading bacteria from Bombyx mori and to produce amylase using isolated bacterial strain. Materials and methods: 50 isolates were isolated from Bombyx mori, SACT2 strain exhibited higher amylase activity and identified as Pantoea gaviniae. The isolated strain was used for amylase production and optimization of media was done using various parameters.Starch degrading bacteria as Pantoea gaviniae was isolated and used for amylase production. The amylase production by the isolated strain was higher of 2.970(U/ml).